2015
DOI: 10.1128/mcb.00926-14
|View full text |Cite
|
Sign up to set email alerts
|

DGCR14 Induces Il17a Gene Expression through the RORγ/BAZ1B/RSKS2 Complex

Abstract: The Dgcr14/Es2 gene is located in a chromosomal region the loss of which has been associated with DiGeorge syndrome, a cause of immunodeficiency, heart defects, and skeletal abnormalities. However, the role of DGCR14 protein remains to be elucidated. Here, I found that DGCR14 protein acts as a coactivator of ROR␥t in T H 17 cells. Biochemical purification of the ROR␥ coregulator complex allowed me to identify the associated DGCR14 protein by matrix-assisted laser desorption ionization-time of flight mass spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 42 publications
0
20
0
2
Order By: Relevance
“…A recent large-scale protein interactome study identified DGCR14 as a non-core component of the spliceosome C complex, suggesting a role in mRNA processing [191193]. Indeed, Dgcr14 apparently regulates IL17a transcription during TH17 cell differentiation in vitro [194], perhaps relevant for immune dysfunction in 22q11DS. In human, DGCR14 is expressed in the heart, brain, and skeletal muscle [195].…”
Section: Main Textmentioning
confidence: 99%
“…A recent large-scale protein interactome study identified DGCR14 as a non-core component of the spliceosome C complex, suggesting a role in mRNA processing [191193]. Indeed, Dgcr14 apparently regulates IL17a transcription during TH17 cell differentiation in vitro [194], perhaps relevant for immune dysfunction in 22q11DS. In human, DGCR14 is expressed in the heart, brain, and skeletal muscle [195].…”
Section: Main Textmentioning
confidence: 99%
“…We recently identified Ess2 (also known as Dgcr14 or Es2) as a transcriptional coregulator of retinoid-related orphan nuclear receptor gamma/gamma-t (RORt) through biochemical purification and matrix-assisted laser desorption ionization-time of flight mass spectrometry analysis (2).…”
Section: Introductionmentioning
confidence: 99%
“…While genetically modified mouse models expressing 22q11DS phenotypes have been reported, immunodeficiency-related genes within 22q11. 2 have not yet been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Όπως αναφέρθηκε και προηγουμένως, η DGCR14 εντοπίζεται στο πυρηνόπλασμα (Sarafidou et al υπό συγγραφή, http://www.proteinatlas.org/) και ορθόλογα μόριά της έχουν ταυτοποιηθεί αποκλειστικά σε ευκαρυωτικούς. Πρόσφατες μελέτες υποδεικνύουν τη συμμετοχή της DGCR14 στη ρύθμιση της έκφρασης της ιντερλευκίνης 17α στα προ-φλεγμονώδη Τβοηθητικά λεμφοκύτταρα (ΤH17-λεμφοκύτταρα) (Takada 2015) και στη διαδικασία της συναρμογής (Noma et al 2014, Dutcher et al 2018.…”
Section: χαρακτηριστικά της πρωτεΐνης Fra10ac1unclassified
“…Ειδικότερα στην ερευνητική εργασία του Takada (2015) έχει δειχθεί ότι η πρωτεΐνη DGCR14 λειτουργεί ως ρυθμιστής ενός μέλους της οικογένειας των πυρηνικών υποδοχέων (υποδοχέας RORγ) οι οποίοι δρουν ως μεταγραφικοί παράγοντες. Ο υποδοχέας αυτός ελέγχει την μεταγραφή γονιδίων που ρυθμίζουν τον κιρκαδικό ρυθμό, την ομοιόσταση των λιπιδίων και της γλυκόζης (Jetten et al 2007) και έχει προταθεί ότι είναι βασικός ρυθμιστής της διαφοροποίησης των ΤH17-λεμφοκυττάρων (Ivanov et al 2006).…”
Section: χαρακτηριστικά της πρωτεΐνης Fra10ac1unclassified